Explore the Method for College English Teaching and Improvement—Basing on the Use of Intelligent Classroom - Ruiyang, Wang; Yaoli, Zhu (Advances in Social Sciences Research Journal, 2022)
Recently, with more and more modern applications being put into use, the college English teaching innovation is facing a huge change. How to integrate those new apps with the real classroom teaching has become a big challenge. This paper will discuss about the process and frequency of using the app (represented by Rainclassroom) , based on the students’ performance, from several aspects, and further providing some benefits deriving from the use of the app .